Fotografia e paisagens da modernidade : Currais Novos/RN de 1950 a 1980 - Medeiros, Gênison Costa de (2010)
This dissertation promotes a dialogue between visual representation and the new cultural geography theory to critically examine the photography representation of an specific urban landscape. The interest here is to explore the ways in which the images of the city of Currais Novos - RN, captured by the photographer Raimundo Bezerra from 1950 to 1980, have taken a great part in shaping people s understanding and imagination of this city s modernizing process. What comes out of this work is the comprehension of that photography permites a geographical study of urban landscape as it can revel perceptions, imaginations, discourses e subjetivities which are based on especific urban cultural dreams and aspirations related to the case studied. So, the aim of this dissertation was to analyse how the discourse of modernity could be seen as part of and impregnated to the urban landscape of Currais Novos by Bezerra s photographs. Then, an intertextual, hermeneutic and phenomenalogical understanding of the geographic object and how it fits within the cultural context was fundamental